The Role of Islamic Financial Institutions in Supporting the Economic Development of Muslim Communities - Rismayana, Rismayana; Azhar, Indana Almas (International Journal of Multidisciplinary Research of Higher Education, 2024)
This research aims to analyze the role of Baitul Maal Wat Tamwil in financing rahn contracts in Islamic financial institutions, the importance of non-bank Islamic financial institutions in providing access to halal financing for the community, especially in the micro and small sectors. This research uses a qualitative approach with a case study method. This type of research is descriptive qualitative which is to analyze the role of the rahn contract applied by the Baitul Maal Wat Tamwil Islamic financial institution. Data sources include primary data, which is obtained through in-depth interviews with two administrators, two members who use rahn contract financing facilities, and three other informants such as field staff and sharia auditors. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and methods to ensure consistency and validity of findings. The results of this study show that access to financing for members through the rahn contract with valuable asset collateral such as gold and motor vehicle owner books. This approach creates a sense of security and trust through a transparent process, thus forming a good relationship between members and institutions. Baitul Maal Wat Tamwil's commitment to sharia principles supports member satisfaction and engagement and community welfare.